A Highly Stereoselective Organocatalytic Approach to Lilial® and Muguesia - Gualandi, Andrea; Emma, Marco Giuseppe; Giacoboni, Jessica; Mengozzi, Luca; Cozzi, Pier Giorgio (Synlett, 2013)
The stereoselective alkylation of aldehydes with benzodithiolylium tetrafluoborate gave a straightforward access to key compounds for the synthesis of fragrances and flavors.
Keywords: organocatalysis; MacMillan catalysts; enamine; alkylation; aldehydes